Maternal obesity and stillbirth at term; placental pathology—A case control study - Åmark, Hanna (PLoS One, 2021)
OBJECTIVE: The aim was to explore the potential role of the placenta for the risk of stillbirth at term in pregnancies of obese women. METHODS: This was a case-control study comparing placental findings from term stillbirths with placental findings from live born infants. Cases were singleton term stillbirths to normal weight or obese women, identified in the Stockholm stillbirth database, n = 264 and n = 87, respectively. Controls were term singletons born alive to normal weight or obese women, delivered between 2002–2005 and between 2018–2019. Placentas were compared between women with stillborn and live-born infants, using logistic regression analyses. RESULTS: A long and hyper coiled cord, cord thrombosis and velamentous cord insertion were stronger risk factors for stillbirth in obese women compared to normal weight women. When these variables were adjusted for in the logistic regression analysis, also adjusted for potential confounders, the odds ratio for stillbirth in obese women decreased from 1.89 (CI 1.24–2.89) to 1.63 (CI 1.04–2.56). CONCLUSION: Approximately one fourth of the effect of obesity on the risk of stillbirth in term pregnancies is explained by umbilical cord associated pathology.